Valuable books of Bessarabian writers from the Rare Book collection of the USARB Scientific Library (Confluenţe Bibliologice, 2022)
The researchers presents information about the valuable works of Bessarabian writers from the collection of rare documents of SL USARB. The collection is a source of information about the political, social and cultural phenomenon that took place in Bessarabia, reﬂected in the books of Bessarabian writers being a good chance for students to research and study the books of Bessarabian writers.